Mapping Hydrothermal Alteration at the Fentale-Dofan Magmatic Segment of the Main Ethiopian Rift - Raggiunti, Martina; Keir, Derek; Pagli, Carolina (Frontiers in Earth Science, 2021)
The Main Ethiopian Rift (MER) is characterized by extensional tectonics and volcanism, associated with active hydrothermal systems, hydrothermal alteration and fumarolic deposits. The spatial distribution of these hydrothermal products and their link with faults and rock types provides important clues to what controls fluid flow in the subsurface. However, little is known about this in the East African Rift. We address this issue with a multidisciplinary approach in the Fentale-Dofan magmatic segment of the MER, an area characterized by intense volcanic and tectonic activity and a geothermal prospect. Primarily we conduct mapping of hydrothermal alteration and fumarolic deposits, and rock lithologies using a surface feature classification technique of multispectral satellite images. Then we interpret the map using a new database of faults and active hydrothermal manifestations such as hot-springs and fumaroles. We find that the surface hydrothermal alteration and deposits are mainly focused near Fentale and the Dofan Volcanic Complex (DVC). At DVC the hydrothermal products are focused on rhyolites on the western side of the volcano, in an area of intense NNE striking, rift parallel faults. At Fentale volcano the hydrothermal products are mainly associated with ignimbrite and show a circular pattern around the volcanic edifice, but also in places follow the NNE striking faults. At Fentale, the more complex association of hydrothermal products and active manifestations around the edge of the ignimbrite suggests formation contacts may also localize fluid flow in places. At both volcanoes the association between hydrothermal products with either the rhyolites and ignimbrites is likely due to them being relatively easily altered (in comparison to basalt), and also their brittle nature allows for fracturing through which localized fluid flow can occur (as opposed to the sediments). The general pattern of hydrothermal products suggests a stronger structural influence at the DVC with respect to Fentale. The presence of hydrothermal products and active hydrothermal manifestations, along with other lines of evidence such as locus of subsurface dike intrusion at the volcanic centres, suggest that discrete and localized magma reservoirs beneath Fentale and the DVC are the heat source for hydrothermal circulation. Our study also demonstrates that geology, including hydrothermal deposits, can be successfully mapped using automated remote sensing based classification.